Anxiety, Beliefs and Covid-19 in Two Periods of the Pandemic in Brazil: A comparative study - Geovanna Santana de Souza Turri; Renata Elly Barbosa Fonte; Luiz Guilherme Lima-Silva; Andre Faro (Revista Costarricense de Psicología)
This research compared evocations regarding the term “coronavirus” during two different periods in the Covid-19 pandemic in Brazil in 2020 — March (beginning of the pandemic in the country) and June (Brazil as the epicenter of the pandemic) —, considering the presence or absence of anxiety symptoms in participants. The methodology adopted the free evocation technique and the Generalized Anxiety Disorder (GAD-2) symptom scale. The sample was composed of 5,961 women and 1,153 men. Participant selection was relegated to convenience sampling by means of an online questionnaire. Results showed that the coronavirus had diff erential impacts among the groups that were assessed and according to the time of data collection. In general, in March, people with anxiety symptoms had a more catastrophic view of the future, while people without those symptoms had a less unfavorable repertoire to adjust to the situation. In June, both groups reported a negative view of the scenario, indicating a decrease or exhaustion in their capacity for psychological adjustment. This suggests the possibility of an increase of some conditions that result in adaptive impairment, exhaustion, and mental illness. Finally, it is important to understand people’s beliefs about the coronavirus at diff erent times of the pandemic because it is a favorable period for the emergence and/or intensification of mental disorders.